The Individual, Network, and Collaborative Competencies, and Investment in Strategic Partnership as Antecedents of the Overall Performance of a Supply Chain Network - Chandej Charoenwiriyakul; Wachararasamee Suntornwanawesshaw (International Journal of Supply Chain Management, 2019)
The prime objective of the current study is to examine the individual, network, and collaborative competencies, and investment in strategic partnership as antecedents of the overall performance of a supply chain network. Additionally, the study has examined the mediating role of collaborative awareness. In this research, the influence of competencies at individual and organizational level has been identified on the practices and performance of supply chain management. The current study has expanded the competencies by studying it at firm level in the management of supply chain. It has been revealed through research findings that collaborative awareness is positively influenced by organizational awareness, which is the individual level competency. The study is among the pioneering studies on the issues. So, current study has used SEM-PLS as statistical tool to answer the research questions raised in this study and research objectives envisaged in the current study. The findings of the current study have provided support to with the hypothesized results. This study will be helpful for policymakers and researchers in examining the link the individual, network, and collaborative competencies, and investment in strategic partnership as antecedents of the overall performance of a supply chain network.